Federale hoofdsteden en nationale culturele instellingen. Lessen voor Brussel uit de voorbeelden van Berlijn, Brasilia, Canberra en Ottowa - Arnaud Bouten; Karel Reybrouck (Brussels Studies)
Given Belgium’s continuing surge towards a greater devolution of powers, the future status of the federal cultural institutions in Brussels remains uncertain. To expand the scope of the political debate, this article provides a comparison of the institutional configuration of national cultural institutions in different federal capitals. This article will examine Berlin, Brasilia, Canberra, Ottawa, and Brussels with a particular focus on the constitutional distribution of powers and intergovernmental cooperation mechanisms. The overview shows that the federal government invariably plays a role in the administration of national cultural institutions in these capital cities. In addition, in most capitals, cultural cooperation mechanisms are established to coordinate federal and state action. On this latter point, there seems to be room for improvement in Brussels.